2014
DOI: 10.1063/1.4880975
|View full text |Cite
|
Sign up to set email alerts
|

The thermal conductivity of clustered nanocolloids

Abstract: We quantify the effect of clustering on the thermal conductivity of colloidal dispersions using silane-treated silica, a system engineered to exhibit reversible clustering under well-controlled conditions. We show that the thermal conductivity increases monotonically with cluster size and spans the entire range between the two limits of Maxwell's theory. The results, corroborated by numerical simulation, demonstrate that large increases of the thermal conductivity of colloidal dispersions are possible, yet ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The two bounds may be taken then to represent the limits of fully dispersed particles (lower limit) and a fully gelled colloid (upper limit), with finite clusters falling in the space between these bounds. Recently, Lotfizadeh et al [8] confirmed this hypothesis by showing that the thermal conductivity of a suspension at fixed volume fraction of primary particles increases monotonically with cluster size and reaches the upper limit of Maxwell's theory in the gel state. In a subsequent study, this behavior was quantified via an analytic model based on Maxwell's theory [10].…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…The two bounds may be taken then to represent the limits of fully dispersed particles (lower limit) and a fully gelled colloid (upper limit), with finite clusters falling in the space between these bounds. Recently, Lotfizadeh et al [8] confirmed this hypothesis by showing that the thermal conductivity of a suspension at fixed volume fraction of primary particles increases monotonically with cluster size and reaches the upper limit of Maxwell's theory in the gel state. In a subsequent study, this behavior was quantified via an analytic model based on Maxwell's theory [10].…”
Section: Introductionsupporting
confidence: 54%
“…In this respect the simulation provides a direct comparison to the predictions of Maxwell's theory. The second reason is based on the previous experimental and theoretical studies that show the enhancement of the thermal conductivity of clustered dispersions is fully captured by the conduction of heat along the solid backbone of the cluster and that other mechanisms, if present, make contributions that are at best within the error bounds of the experimental measurements [6][7][8][10][11][12][13]. The Monte Carlo method used here is based on the work of Van Siclen [14].…”
Section: Monte Carlo Methods For the Thermal Conductivity Of Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 16 compares simulations and experimental measurements for SiO 2 nanoparticles dispersed into water for various volume fractions. Their average radius of gyration and effective conductivity were measured in the literature [ 45 ]. The aggregates consist of approximately particles, and their fractal dimension is approximately [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, this strategy has been recently implemented in heat exchanger devices, by adding an aqueous suspension of colloidal silica so as to obtain a stable system, ranging from the fully dispersed state up to the colloidal gel one, leading to improvements of the thermal conductivity up to 20% [92]. In this frame, open clusters (having low d f ) should allow a faster transport of the heat when compared to their equally sized, more compact counterparts, as a more direct heat flow through the clusters occurs.…”
Section: Heat Exchangers and Insulating Materialsmentioning
confidence: 99%